The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12886-019-1082-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual implications of digital device usage in school children: a cross-sectional study

Abstract: PurposeTo evaluate the use of digital devices, reading habits and the prevalence of eyestrain among urban Indian school children, aged 11–17 years.MethodsThe study included 576 adolescents attending urban schools who were surveyed regarding their electronic device usage. Additional information on the factors that may have an effect on ocular symptoms was collected.ResultsTwenty percent of students aged 11 in the study population use digital devices on a daily basis, in comparison with 50% of students aged 17. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 26 publications
8
66
1
1
Order By: Relevance
“…Smartphones and laptops were the most frequently used devices reported in similar studies by Ichhpujani et al and Margareta et al 20,21 Students used digital devices mainly for social networking and college projects.…”
Section: Digital Device Preferencementioning
confidence: 67%
“…Smartphones and laptops were the most frequently used devices reported in similar studies by Ichhpujani et al and Margareta et al 20,21 Students used digital devices mainly for social networking and college projects.…”
Section: Digital Device Preferencementioning
confidence: 67%
“…Further biases may come from the years between data collection, as recent evidence from studies in adults suggests that the rapid increase in the use of computers and handheld devices has led to an increase in symptomology [44,63]. It is pertinent to note that the data from the current study was collected at a time not dissimilar to the other studies already mentioned.…”
Section: Prevalence Of Symptomsmentioning
confidence: 91%
“…In general, increasing symptom prevalence has been found with increasing age [61,62]. Rouse et al [62] found an increase in CISS scores of 2.6 when comparing the scores of adults to children, presumably due to greater periods of prolonged near work for adults [61] and increased duration of handheld electronic devices for leisure [44]. Our students were on average nearly 2 years older (13.17 ± 1.4 years) than those in the CITT group's [41] earlier study (mean 11.4 ± 2.2 years), and this age difference may account for a portion of the increase in symptoms found in our students.…”
Section: Prevalence Of Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, students aged 7-12 years, who used a smartphone for more than 4 h a day over a period of at least 4 months, presented with acute acquired comitant esotropia (17). A study in India (18) included 576 adolescent students and reported a significant correlation in the practice of lying down while using a screen-enabled device to symptoms of digital eye strain (27%). By the end of the day 18% of the students experienced eye strain, attributed to digital screen use.…”
Section: Negative Effects Of Videogaming Problematic Internet Use Amentioning
confidence: 99%